Controls on 231Pa and 230Th in the Arctic Ocean - Luo, Yiming; Lippold, Jörg (Geophysical research letters, 2015)
The distributions of 230Th and 231Pa in the Arctic Ocean are not well understood. In order to examine the Arctic 231Pa/230Th system and therefore to shed light on the future use of Arctic sedimentary 231Pa/230Th, we developed a 2-D scavenging model modified from an Atlantic model. Tuned with reasonable parameters that are consistent with Eurasian Basin geographic settings, the model can reproduce most of the features of the 230Th and 231Pa water column profiles as well as the sedimentary 231Pa/230Th distribution patterns and suggests that the sedimentary 231Pa/230Th in the Eurasian Basin is mainly controlled by the deep water circulation. In our attempt to reproduce the sedimentary 231Pa/230Th patterns during the last glacial, we found that circulation strength in the Eurasian Basin at shallower depths may have been stronger than today.